2016
DOI: 10.3892/or.2016.4957
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide induces the cell apoptosis of osteosarcoma cells through the TRAIL pathway

Abstract: Research on triptolide, a diterpenoid epoxide found in the Thunder God Vine Tripterygium wilfordii, has increased our knowledge of the pharmacology, pharmacokinetics, toxicology and clinical application of this agent. In the present study, we aimed to identify the effects of triptolide on the apoptosis of osteosarcoma cells and to evaluate the anti-proliferative action of this agent. MG-63 cells were treated either with various doses of triptolide (50, 100 or 200 nM) or DMSO for 6, 12 and 24 h. Treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The results of western blot analysis in the present study indicate that triptolide suppresses ERK1/2 activation and inhibits HIF1-α expression in breast cancer cells. Triptolide has been demonstrated to regulate several key signaling pathways in tumor progression, including the phosphatidylinositol-4,5-bisphosphate 3-kinase/Akt/Serine/threonine-protein kinase mTOR, tumor necrosis factor (TNF)-related apoptosis-inducing ligand and nuclear factor (NF)-κB signaling pathways ( 26 , 27 ). The present study examined Akt phosphorylation following triptolide treatment and identified a slight decrease in p-Akt, although this decrease was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…The results of western blot analysis in the present study indicate that triptolide suppresses ERK1/2 activation and inhibits HIF1-α expression in breast cancer cells. Triptolide has been demonstrated to regulate several key signaling pathways in tumor progression, including the phosphatidylinositol-4,5-bisphosphate 3-kinase/Akt/Serine/threonine-protein kinase mTOR, tumor necrosis factor (TNF)-related apoptosis-inducing ligand and nuclear factor (NF)-κB signaling pathways ( 26 , 27 ). The present study examined Akt phosphorylation following triptolide treatment and identified a slight decrease in p-Akt, although this decrease was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Triptolide (T10) is a major active ingredient extracted from the Chinese herb, Tripterygium wilfordii hook F (TWHF) [ 5 ]. It has been shown that T10 can effectively inhibit many kinds of cancers [ 6 ], including osteosarcoma [ 7 , 8 ], pancreatic cancer [ 9 , 10 ], breast cancer [ 11 , 12 ], and leukemia [ 13 , 14 ]. Recent studies have demonstrated T10 to be effective in ameliorating some non-cancer pain status, such as neuropathic pain [ 5 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…CatB activity is significantly increased following 1-2 h of exposure to TRAIL [149]. Triptolide inhibits cell viability and proliferation, and induced apoptosis in OS cell line MG-63 [148]. Previous studies by Owa et al, support this finding, citing that triptolide induces lysosomal-mediated programmed cell death in MCF-7 BCa cells through CatB and caspase-3 [152].…”
Section: The Role Of Cathepsins In Primary Bone Cancer and Metastasesmentioning
confidence: 82%
“…Intriguingly, CatB has been discovered to also demonstrate anticancer effects in the OS cell line MG-63, which is mediated through the activation of the DR-5/p53/Bax/caspase-9/-3 signaling pathway and the DR-5/FADD/caspase-8/lysosomal/cathepsin B/caspase-3 signaling pathway [148]. The release of CatB from the lysosome into the cytosol induces cell death in vitro [44].…”
Section: The Role Of Cathepsins In Primary Bone Cancer and Metastasesmentioning
confidence: 99%
See 1 more Smart Citation